Modulation of macrophage phenotype for spinal cord injury repair - Tatic, Natalija (2020)
Upon traumatic injury (SCI), spinal cord capacity for regeneration is limited and one of the main reasons may be the chronic inflammation. It can be then hypothesized that strategies aiming to resolve inflammation would contribute to spinal cord repair. Among different options to achieve that goal, mesenchymal stem cells (MSC) and ECM-based hydrogels have been both described as being immunomodulatory. The aim of this thesis then was to explore the potential of stem cells of dental apical papilla (SCAP) and extracellular matrix (ECM) hydrogels to mitigate SCI inflammation. SCAP had previously been shown to reduce tumour necrosis factor alpha (TNFα) gene (Tnf) expression in vitro, whilst ECM hydrogels had been shown to induce the M2-like phenotype in naïve monocytes. First, rheological properties of spinal cord and bone ECM hydrogels of 8mg/mL (S8 and B8) were measured. To increase S8 gelation rate and modulus fibrin was added to S8 pre-gel solutions at a 75/25 ratio (S/F). To investigate anti-inflammatory properties of hydrogels and SCAP, a mouse microglia cell line was used (BV2 cells). S8 solubilised, i.e. dispersed in medium before hydrogel formation is completed, reduced LPS-induced increase in inducible nitric oxide synthetase and arginase 1 gene expression ratio (Nos2/Arg1). Solubilised B8 reduced Tnf expression. SCAP reduced Nos2/Arg1 ratio and Tnf expression. S8+SCAP reduced Nos2/Arg1, whilst B8+SCAP reduced Nos2/Arg1 ratio and Tnf expression. To get a better understanding of how SCAP metabolism, free or incorporated in S8 ECM hydrogels, could be influenced by pro-inflammatory cytokines, a metabolomic analysis of cell supernatants was performed. SCAP stimulated with TNFα and interferon gamma (IFNγ) activated kynurenine pathway. Anti-inflammatory lipids were detected in scECM. SCAP+scECM had altered antioxidative amino acid and lipid profile. Still, in SCAP+scECM+stimuli the kynurenine pathway was enhanced and anti-inflammatory molecules were more abundant compared to stimulated SCAP alone. Thus, SCAP combined with ECM hydrogels may be considered as a strategy to mitigate SCI inflammation.